1999
DOI: 10.1074/jbc.274.14.9828
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1-mediated Neuroprotection against Oxidative Stress Is Associated with Activation of Nuclear Factor κB

Abstract: The role of insulin-like growth factor 1 (IGF-1) for the treatment of neurodegenerative disorders, such as Alzheimer's disease, has recently gained attention. The present study demonstrates that IGF-1 promotes the survival of rat primary cerebellar neurons and of immortalized hypothalamic rat GT1-7 cells after challenge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(127 citation statements)
references
References 52 publications
9
117
0
1
Order By: Relevance
“…Previous reports have shown that IGF-1, its receptors, and binding proteins are all upregulated in response to ischemia and other neurodegenerative conditions (Schwab et al, 1997;Beilharz et al, 1998;Fernandez et al, 1998). This upregulation appears to provide neuroprotection, because exogenous IGF-1 both in vivo and in vitro protects neurons from different types of injury (Tagami et al, 1997;Heck et al, 1999;Guan et al, 2000;Wang et al, 2000;Yamaguchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports have shown that IGF-1, its receptors, and binding proteins are all upregulated in response to ischemia and other neurodegenerative conditions (Schwab et al, 1997;Beilharz et al, 1998;Fernandez et al, 1998). This upregulation appears to provide neuroprotection, because exogenous IGF-1 both in vivo and in vitro protects neurons from different types of injury (Tagami et al, 1997;Heck et al, 1999;Guan et al, 2000;Wang et al, 2000;Yamaguchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…The expression of IGF-1 and its binding proteins are altered in response to brain ischemia (Lee et al, 1996;Schwab et al, 1997;Beilharz et al, 1998), and exogenous administration of IGF-1 significantly reduces neuronal loss in different models of cerebral ischemia (Johnston et al, 1996;Tagami et al, 1997;Guan et al, 2000;Wang et al, 2000). Furthermore, it has been shown that IGF-1 protects cultured neurons against diverse forms of injury, including hypoxia and oxidative stress (Heck et al, 1999;Yamaguchi et al, 2001).…”
Section: Abstract: Global Cerebral Ischemia; Hypoxia-inducible Factomentioning
confidence: 99%
“…178 Thus PKB/Akt appears to function in parallel with NIK to activate IKK. Similarly, the PI3K-PKB/Akt pathway ( Figure 2) is involved in the activation of NF-B by PDGF, 179 insulin, 180 IGF-1 181 and NGF. 182 Activation of NF-B has a role in the anti-apoptotic signaling of these cytokines.…”
Section: Role Of the Rel/nf-b Transcription Factors In The Control Ofmentioning
confidence: 99%
“…(Heck et al, 1999). In unstressed cells, NF-kB is retained in the cytoplasm as a heterodimer with IkB.…”
Section: Nf-kbmentioning
confidence: 99%